Who's afraid of atmospheres (and of their authority)? (Lebenswelt. Aesthetics and philosophy of experience., 2014)
An atmosphere possesses and exercises authority over the perceiver and his felt-body. This authority (a ‘numinous’ one) exists in the proper sense only when it prevails over our resistance and we cannot access a further critical level. This is because an atmosphere that I feel externally, as poured out into the surrounding space, is mine not because I possess it, but because it concerns me.Its normativity, moreover, is not so much discreet but rather loosely diffused into a situation and yet it is able to inhibit any critical distance in those who come across it, especially if unexpectedly. This atmospherological approach implies of course a reflection about the ethical consequences of our ‘necessary’ felt-bodily feelings. Even if the manipulative appearance is implicit in every practice that generates an atmosphere, it’s true thatonly by acquiring a better atmospheric ‘competence’ (both as thinkers and as perceivers) we can really learn how not to be grossly manipulated. An atmosphere is maybe less manipulative when it allowsaquick alternation between an uncritical-pathicimmersion and a critical-rational emersion, namely, between an emotional mood and a more analytical one.